Tensile properties of a Fe-32Mn-6Si shape memory alloy - Bouraoui, T.; Jemal, F.; Ben Zinebc, T. (Проблемы прочности, 2008)
The tensile properties of a Fe-32Mn-6Si shape memory alloy were investigated. It was found that tensile properties depend on temperature, heat treatment and material structure. The relationships of martensitic transformation, tensile properties, and shape memory effect are discussed. Finally, we propose a macroscopic one-dimensional constitutive law describing the thermomechanical behavior in tensile loading. Numerically obtained results are close to the experimental ones.